A New Formulation of Probiotics Attenuates Calcipotriol-Induced Dermatitis by Inducing Regulatory Dendritic Cells - Xu, Beilei; Ling, Shiqi; Xu, Xiaoqiang; Liu, Xiaochun; Wang, Ao; Zhou, Yuan; Luo, Yang; Li, Wei; Yao, Xu (Frontiers in Immunology, 2021)
Atopic dermatitis (AD) is a recurrent chronic inflammatory skin disease affecting up to 30% of the children population, and immuno-regulatory therapy that could modify the course of the disease is urgently needed. Probiotics have demonstrated therapeutic effects on AD and could potentially regulate the disease process. However, the efficacy of probiotics for AD is inconsistent among different studies, which is mainly due to the elusive mechanism and different species and (or) strains used. In this study, we designed a mixture of five strains of probiotics (named IW5) and analyzed the effect and mechanism of IW5 on MC903-induced AD-like dermatitis. We found that IW5 significantly alleviated skin inflammation of the MC903-induced AD in mice. Administration with IW5 induced increased production of regulatory T cells and regulatory dendritic cells (DCregs) in the mesenteric lymph nodes. We also found that the diversity of the gut microbiota in the mice with MC903-induced dermatitis was increased after IW5 administration, and the level of butyrate in the gut was elevated. In cell culture, butyrate induced the production of DCregs. Our study revealed the therapeutic effects of a newly designed probiotics mixture and uncovered a possible mechanism, providing a foundation for future clinical studies.